Pengaruh Bimbingan Pra-Nikah di Kantor Urusan Agama terhadap Kesiapan Rumah Tangga Muda Studi Kasus : Kantor Urusan Agama Pancoran Mas - Hamidah, Zilfa; Tubagus Miftahuddin (El-Izdiwaj: Indonesian Journal of Civil and Islamic Family Law, 2025)
This study aims to analyze the influence of pre-marital counseling on the marital readiness of young couples, taking a case study at the Office of Religious Affairs (KUA) in Pancoran Mas. Facing the complexity of challenges in the early years of marriage, this research examines the effectiveness of the existing counseling program and explores the urgency of developing a sustainable counseling model. The research method employed is a mixed-methods approach, integrating quantitative and qualitative paradigms. Quantitative data were collected through questionnaires from 39 respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Qualitative data were obtained through in-depth, semi-structured interviews with seven key figures, comprising community leaders and internal KUA officials. The quantitative analysis a positive influence of pre-marital counseling on readiness, where the variables of Perception and Competence significantly affect Readiness. However, a significant discriminant validity issue was found between the Material and Readiness variables, along with a suboptimal model fit (R-Square 0.475), indicating the limitations of the current model. This finding is reinforced by the qualitative results, which consistently highlight a gap between the theoretical knowledge provided in pre-marital counseling and the practical challenges faced post-marriage. The key figures strongly recommend a continuous counseling program during the first year of marriage as a solution to enhance family resilience. The synthesis of both approaches concludes that while pre-marital counseling provides a positive contribution, a transformation towards a more holistic and sustainable guidance model is necessary to effectively equip young couples.